Screening for Sphingolipid-Storage Diseases - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
A simple fluorescence assay was used to detect cells from patients with sphingolipidoses in a masked study at the Mayo Clinic, Rochester, MN.